"In the shadows of hierarchy": Intergovernmental governance in Canada and the European Union. (22nd May 2013) - Bakvis, Herman
Abstract The articles in this issue suggest that intergovernmental governance takes a different form in Canada and the EU, raising questions about the transference of practices and institutions from one to the other. In both systems, non‐hierarchical modes of governance provide coordination in social policy. Hierarchy also plays a role, though not in a manner that one might expect. In the EU, hierarchy is tempered by members' direct participation in policy formulation. In Canada, hierarchy is important, but within rather than between governments, resulting in executive dominance of the intergovernmental process at the expense of devolving power to civil society and sub‐provincial governments.